Analisis Penerapan Peraturan Daerah Tentang Pengelolaan Sampah - Bella Dian Nusantara; Teguh Yuwono; Tri Yuningsih (JOPPAS: Journal of Public Policy and Administration Silampari, 2023)
The purpose of this study is to find out the application of policy No. 2 of 2011 concerning Waste Management. However, this research only focuses on the tourism area of Jakat Beach. This study uses a qualitative method, the research data is sourced from primary and secondary data, to analyze the data through the stages of data condensation, data display, verification and drawing conclusions. The results of the study show that the application of regional regulation No. 02 of 2011 concerning waste management in the coastal tourism area of the Jakat City of Bengkulu has not fully proceeded according to the purpose of the issuance of the regional regulation. Confirmed that there is no program for reducing and handling waste properly. Keywords: Waste management, community participation, tourist attraction